Compositional and structural characterization of eleven types of lignocellulosic biomass and its potential application in obtaining nanopolysaccharides and producing polyhydroxyalkanoates (Scientia Agropecuaria, 2024)
The valorization and use of lignocellulosic biomass from food processing to obtain value-added products is crucial to improve sustainability and reduce waste management costs. This potential for cost reduction is a reason for optimism, as it allows agro-industrial waste to be transformed into valuable resources, contributing to the circular economy. This study focused on the compositional and structural characterization of eleven types of lignocellulosic biomass (LCB) to evaluate their potential in producing nanopolysaccharides and polyhydroxyalkanoates. Parameters such as humidity, ash, proteins, extractives, structural carbohydrates, and lignin were analyzed in passion fruit peels, artichoke bracts, asparagus peels, lemon peels, orange peels, avocado seed, potato peels, cassava peels, sugar cane bagasse, rice husk, and rice straw. The results showed that fruit peels and other waste had a high extractive content (28.05%), while the content of lignin and structural carbohydrates varied between 69.66% and 30.53% and 22.2% and 8.84%, respectively. In addition to the characterization, this BLC's potential for producing biopolymers was explored, highlighting its relevance in various industries such as food and materials engineering. These findings underline the importance of using local natural resources sustainably, opening new opportunities to develop innovative applications such as pickering emulsions, biodegradable packaging, aerogels, hydrogels, and functional foods. These applications represent promising areas for future research and technological development.
Keywords: circular economy; biorefinery; agricultural waste; agro-industrial waste; structural carbohydrates; high-performance liquid chromatography; biopolymers